The Motivation of the Foreign Students of Vilnius University to Learn Lithuanian as a Second Language - Bružaitė-Liseckienė, Justina (Vilnius University Open Series, 2023)
The article analyses the motivation of students of Vilnius University to learn Lithuanian as a second language and determines which sociolinguistic factors have a significant influence on students’ motivation. The main research tool is the questionnaire on motivation to learn Lithuanian as a L2, which was created based on the theories and questionnaires of two linguistic researchers on learning motivation, Robert Gardner (2004) and Zoltán Dörnyei (2010). 89 students of Vilnius University, beginners of Lithuanian language as L2 students, participated in the study. 50 subjects were medical students, 39 were students attending Lithuanian language courses as Erasmus exchange students. The study found that motivation to learn Lithuanian is usually significantly influenced by students’ main reason for choosing to learn Lithuanian. Those who emphasised that they were learning Lithuanian because the course was mandatory for them (i.e., the majority of medical students) had, in most cases, lower motivation to learn Lithuanian. The latter students should be distinguished from those who cite living in Lithuania or the desire to communicate in Lithuanian as reasons for learning Lithuanian. The motivation of these subjects to learn Lithuanian is related to the image of the ideal self, integrative motivation, positive state of the Lithuanian language learning environment, attitude toward the Lithuanian community, interest in L2 learning, and effort to learn Lithuanian. This shows a much closer connection not only with the Lithuanian language itself, but also with the context in which it is learned and used. Significant differences in motivation to learn Lithuanian are also found between medical students and Erasmus exchange students. The motivation of medical students differed from that of Erasmus students, who scored significantly higher only on preventive motivation. Erasmus students, on the other hand, learn Lithuanian under more general cultural and educational incentives (greater interest in Lithuanian culture, motivation to learn L2).
Keywords: motivation; second language acquisition; Lithuanian as a second language; sociolinguistic factors; language learning motivation questionnaire